Influence of ECAP passes on Zn–Li–Mn alloys: mechanics, corrosion, and osteogenesis - Tian, Jing; Hu, Yaojia; Yan, Chengyue; He, Zhuoxuan; Li, Shikai; Li, Huachi; Huang, Jinghui (Frontiers in Materials, 2026)
IntroductionBiodegradable zinc is a promising base metal for temporary orthopedic fixation; however, its insufficient strength has limited its use at load-bearing sites.MethodsWe designed a Zn–Li–Mn system and refined its microstructure by equal-channel angular pressing (ECAP). The number of ECAP passes was tuned to investigate its effect on mechanical and electrochemical properties.ResultsIncreasing the number of passes resulted in significant improvements in mechanical response, reaching an ultimate tensile strength of approximately 450 MPa with favorable elongation (up to 76.6% at 12 passes). Strengthening occurred through a combination of grain refinement, dislocation hardening, and second-phase contributions. Electrochemical tests and long-term immersion in Hank’s solution revealed a progressive enhancement in corrosion resistance, with the average corrosion rate decreasing from approximately 34.60 to 26.66 μm year-1 between 8 and 16 passes. Microstructural uniformity reduced localized attack at second phases and grain boundaries.DiscussionIn vitro studies with MC3T3-E1 cells confirmed cytocompatibility and demonstrated enhanced osteogenic activity compared to titanium controls. This included increased alkaline phosphatase levels, stronger mineral deposition, and upregulated osteogenesis-related genes. These findings suggest that ECAP effectively optimizes strength, ductility, and corrosion resistance in Zn-based alloys, supporting their potential as next-generation biodegradable implants for orthopedic applications.